Biofilm formation by Candida albicans and Streptococcus mutans in the presence of farnesol: a quantitative evaluation - Fernandes, Renan Aparecido [UNESP] (2016)
The aim of this study was to evaluate the effect of the QS molecule farnesol on single and mixed species biofilms formed by Candida albicans and Streptococcus mutans. The anti-biofilm effect of farnesol was assessed through total biomass quantification, counting of colony forming units (CFUs) and evaluation of metabolic activity. Biofilms were also analyzed by scanning electron microscopy (SEM). It was observed that farnesol reduced the formation of single and mixed biofilms, with significant reductions of 37% to 90% and 64% to 96%, respectively, for total biomass and metabolic activity. Regarding cell viability, farnesol treatment promoted significant log reductions in the number of CFUs, ie 1.3–4.2 log10 and 0.67–5.32 log10, respectively, for single and mixed species biofilms. SEM images confirmed these results, showing decreases in the number of cells in all biofilms. In conclusion, these findings highlight the role of farnesol as an alternative agent with the potential to reduce the formation of pathogenic biofilms.